1985
DOI: 10.1002/aic.690310605
|View full text |Cite
|
Sign up to set email alerts
|

Rapid hydropyrolysis of softening coal particles—A modeling study. Part I: Model formulation and parameter values

Abstract: A mathematical model is developed for rapid hydropyrolysis of softening coal particles. It is aimed to represent previously measured effects of pressure and particle size on product yields. The model includes a global chemical reaction scheme combined with diffusional transport of hydrogen dependent on the transient physical properties of the coal. Model predictions are compared with experimental data in a companion paper. The objective of this study was to define and formulate a mathematical model for rapid h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1989
1989
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The small species formed in the metaplast then have a high enough vapor pressure to be released as tar. Some of the original data for coal hydropyrolysis was obtained by Anthony et al and Suuberg et al with subsequent development of a hydropyrolysis model . Recently, Guan et al developed a simple modification to the CPD model to describe coal hydropyrolysis.…”
Section: Modifications To Extend Cpd Model Capabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The small species formed in the metaplast then have a high enough vapor pressure to be released as tar. Some of the original data for coal hydropyrolysis was obtained by Anthony et al and Suuberg et al with subsequent development of a hydropyrolysis model . Recently, Guan et al developed a simple modification to the CPD model to describe coal hydropyrolysis.…”
Section: Modifications To Extend Cpd Model Capabilitymentioning
confidence: 99%
“…Some of the original data for coal hydropyrolysis was obtained by Anthony et al 194 and Suuberg et al 195 with subsequent development of a hydropyrolysis model. 196 Recently, Guan et al 197 developed a simple modification to the CPD model to describe coal hydropyrolysis. The hydropyrolysis and crosslinking reactions are assumed to both decrease the amount of metaplast in the coal during pyrolysis according to…”
Section: Modifications To Extend Cpd Modelmentioning
confidence: 99%
“…Drawing on the work of Van Krevelen (1961) and Neavel ( 1 982) and studies in this laboratory (Schaub et al, 1985a, b;Fong et al, 1985Fong et al, , 1986a, it was concluded that softening occurs when a critical temperature and concentration of a thermally-derived plasticizing agent, known as metaplast, are reached. Some metaplast is assumed to preexist in the coal as a bitumenlike material.…”
Section: General Descriptionmentioning
confidence: 99%